METODE TAHFIDZ KOLABORATIF : MITIGASI KELEMAHAN HAFIDZ DI AKHIR ZAMAN - Siti Rohmatul Ummah (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
Memorizing the Qur'an by following the guidance of the Prophet and the Companions means not only memorizing orally, but also understanding and applying the teachings in daily life. The Prophet once warned that there would be a period in the future where many people would only recite the Qur'an orally without internalizing and applying it. To overcome this, the author conducted research to develop a collaborative tahfidz method. This method aims to make memorizers not only memorize verses but also understand their meaning so that they can apply them in life. This research uses a descriptive qualitative approach by analyzing the tahfidz methods that are common in Indonesia and formulating a new, more comprehensive method. The proposed method integrates the basic method and the development method, where the development method serves as the framework and the basic method as the implementation technique. With this method, memorizers can set memorization targets and time according to their abilities and understand each verse memorized, so that the memorization process becomes more effective, increases the quantity and quality of memorization, and has a positive impact on their lives.